Navigating the Financial Aid Process: Borrowing Outcomes among First-Generation and Non-First-Generation Students. Issue 1 (May 2017) - Furquim, Fernando; Glasener, Kristen M.; Oster, Meghan; McCall, Brian P.; DesJardins, Stephen L.
A growing number and proportion of students rely on student loans to assist with the costs of postsecondary education. Yet little is known about how first-generation students use federal loans to finance their education. In this article, we examine each of the decisions that culminate in student indebtedness: the decision to apply for aid, whether to borrow, and how much to borrow. We find significant differences by generational status at each step of the student borrowing process. First-generation students are more likely to apply for financial aid, borrow, and take out larger loans than their peers, after controlling for a rich set of covariates for costs and financial resources. We find that student characteristics cannot fully explain these observed differences in borrowing outcomes across generations.